2022
DOI: 10.3892/ol.2022.13420
|View full text |Cite
|
Sign up to set email alerts
|

Chronic restraint stress promotes gastric epithelial malignant transformation by activating the Akt/p53 signaling pathway via ADRB2

Abstract: The etiology of gastric cancer is associated with infectious, environmental and dietary factors, as well as genetic background. Additionally, emerging evidence has supported the vital role of chronic emotional stress on gastric carcinogenesis; however, the underlying mechanism remains unclear. The present study aimed to investigate the effects of chronic stress and a detrimental diet on gastric malignant epithelial transformation in rats. Therefore, 26 Wistar rats were randomly divided into the following four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…Furthermore, Feng et al (2012) have demonstrated that increased glucocorticoid concentrations during chronic restraint stress reduced p53 levels and function, which in turn contributed to irradiation-induced tumorigenesis. Most recently, Zong et al (2022) have pointed toward a key role of beta-adrenergic signaling in chronic stress-induced malignant transformation of gastric epithelial cells through the induction of p53 protein degradation. Aside from the impact on tumorigenesis, stress hormones can stimulate the proliferation of cancer cells by activating various signaling pathways and promoting cell division.…”
Section: Chronic Stress and Cancer—a Bidirectional Relationshipmentioning
confidence: 99%
“…Furthermore, Feng et al (2012) have demonstrated that increased glucocorticoid concentrations during chronic restraint stress reduced p53 levels and function, which in turn contributed to irradiation-induced tumorigenesis. Most recently, Zong et al (2022) have pointed toward a key role of beta-adrenergic signaling in chronic stress-induced malignant transformation of gastric epithelial cells through the induction of p53 protein degradation. Aside from the impact on tumorigenesis, stress hormones can stimulate the proliferation of cancer cells by activating various signaling pathways and promoting cell division.…”
Section: Chronic Stress and Cancer—a Bidirectional Relationshipmentioning
confidence: 99%